Case study -- Guatemalan raspberries and cyclospora: food safety in food security and food trade - Calvin, Linda; Flores, Luis; Foster, William E. (International Food Policy Research Institute, 2003)
The Guatemalan raspberry industry began exporting to the United States in the late 1980s, filling a market niche in the spring and fall when supplies were low. By 1996, Guatemalan raspberry exports were increasing rapidly, up 113 percent from the previous season. That spring and early summer, the U.S. Centers for Disease Control and Prevention (CDC) and Health Canada received reports of more than 1,465 cases of food-borne illness from Cyclospora, a protozoan parasite. Although no one died, the large number of cases generated substantial adverse publicity. Initially, investigators linked the outbreak to California strawberries, but they finally decided that it was associated with Guatemalan raspberries. This case study reviews the efforts to resolve this food safety problem. It is a cautionary tale about the serious impact a food safety outbreak can have on a promising industry. -- from Text